The analgesic benefit of Pericapsular Nerve Group (PENG) block in hip arthroscopic surgery: a retrospective pragmatic analysis at an academic health center. Issue 12 (25th August 2022) - Patel, Vanisha; Patel, Vivesh; Abdallah, Faraj; Whelan, Daniel; Bansal, Shikha; Gabra, Martino; Brull, Richard
Abstract : Introduction: The novel pericapsular nerve group (PENG) block has recently been reported to provide effective motor-sparing local anesthetic-based analgesia to the hip joint. We aimed to evaluate the analgesic efficacy and safety of a preoperative PENG block among patients undergoing ambulatory hip arthroscopic surgery where systemic analgesia is the gold standard. Methods: We conducted a single-center, retrospective pragmatic exploratory cohort study of consecutive outpatient hip arthroscopic surgery cases from January 2017 to March 2019. We identified 164 cases in which patients received general anesthesia with or without a preoperative PENG block. The primary analgesic outcome measures were time to first postoperative analgesic request, intraoperative and postoperative opioid consumption (intravenous morphine equivalent), and postoperative pain severity (visual analog scale 10 cm scale ranging from 0=no pain to 10=severe pain) in hospital. Secondary outcomes included duration of stay in the postanesthesia care unit, opioid-related side effects, time to discharge readiness, and block-related complications. Results: Seventy-five cases received a preoperative PENG block and 89 cases received systemic analgesia alone. The addition of a PENG block reduced intraoperative (6.6 mg vs 7.5 mg, difference: 0.9 mg; 95% CI 0.2 to 1.7; p=0.01) and postoperative (10.7 mg vs 13.9 mg, difference: 3.2 mg; 95% CI 0.9 to 5.5; p=0.01) intravenous morphine consumption, as well as the mean (3.5 vs 4.2, difference: 0.7; 95% CI 0.1 to 1.3; p=0.03) and highest (5.5 vs 6.5, difference: 1.0; 95% CI 0.2 to 1.7; p=0.02) postoperative pain severity scores in hospital. The PENG block did not prolong the time to first analgesic request (15.8 min vs 12.3 min, difference: 3.5 min; 95% CI −9.0 to 2.0; p=0.23). Fewer patients in the PENG group experienced postoperative nausea and vomiting compared with systemic analgesia alone (36% vs 52%, OR 1.9; 95% CI 1.0 to 3.6; p=0.02), while the PENG block expedited discharge readiness (165.0 min vs 202.8 min, difference: 37.8 min; 95% CI 2.9 to 72.3; p=0.04). No block-related complications were noted in any patient. Discussion: Based on our retrospective dataset, this pragmatic exploratory cohort study suggests that a preoperative PENG block is associated with questionable improvements in postoperative in-hospital analgesic outcomes which may or may not prove to be clinically relevant when compared with systemic analgesia alone for patients undergoing hip arthroscopic surgery. This small signal should be investigated in a prospective randomized trial.